2023
DOI: 10.1111/apa.16953
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of severe congenital heart defects in live‐born infants in Norway 2017–2020

Gunnar Wik,
Jarle Jortveit,
Vasilis Sitras
et al.

Abstract: AimThe aims of this nationwide retrospective cohort study were to determine the time and causes of detection of severe congenital heart defects (CHDs) in live‐born infants in Norway between 2017 and 2020.MethodsInformation regarding live‐born infants with severe CHDs was retrieved from national registries and medical records.ResultsA total of 219 776 infants were born in Norway from 01.01.2017 to 31.12.2020. Severe CHDs were diagnosed in 442 (0.2%) infants. Of these, 376 (85%) infants were diagnosed either pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A nationwide Norwegian study by Wik et al. showed that most infants with severe congenital heart diseases (CHD) were identified before they were discharged from hospital, but some infants were still sent home undiagnosed 3 . Meberg comments on the findings and suggests how screening could be improved 4 .…”
Section: Clinicians Are Still Missing Critical Congenital Heart Defec...mentioning
confidence: 99%
“…A nationwide Norwegian study by Wik et al. showed that most infants with severe congenital heart diseases (CHD) were identified before they were discharged from hospital, but some infants were still sent home undiagnosed 3 . Meberg comments on the findings and suggests how screening could be improved 4 .…”
Section: Clinicians Are Still Missing Critical Congenital Heart Defec...mentioning
confidence: 99%
“…The number of missed cases seems to have been fairly stable, about 10%, over time. 1,6,7,12 Although most of them survive, including all the newborn infants in the Wik et al 1 study, there is still potential for some long-term sequelae. As Wik et al 1 found, in agreement with others, 3,6,12,13 coarctation of the aorta and hypoplastic aortic arch are the most frequently missed critical CHDs.…”
mentioning
confidence: 98%
“…1,6,7,12 Although most of them survive, including all the newborn infants in the Wik et al 1 study, there is still potential for some long-term sequelae. As Wik et al 1 found, in agreement with others, 3,6,12,13 coarctation of the aorta and hypoplastic aortic arch are the most frequently missed critical CHDs. We need better methods and screening strategies to target these, and the other CHDs that are missed most often.…”
mentioning
confidence: 98%
See 2 more Smart Citations